Differential diagnosis of precocious puberty in girls during the COVID-19 pandemic: a pilot study - Huihui Sun; Yi Qian; Naijun Wan; Lili Liu (BMC, 2023)
Abstract Background To investigate the differential diagnosis of girls aged 6 to 8 years with idiopathic premature thelarche (IPT) and central precocious puberty (CPP) during the COVID-19 pandemic. We explored predicted adult height (PAH) discrepancy to guide appropriate diagnosis and treatment. Methods From January 2020 to December 2021, Chinese girls aged 6 to 8 years with precocious puberty were recruited. They were divided into IPT and CPP groups. Clinical characteristics, including height, weight, body mass index (BMI), basal luteinizing hormone (LH), oestradiol, uterine length and volume, follicle numbers (d > 4 mm) and bone age (BA) were recorded. We analysed differential diagnosis and PAH discrepancy in both groups. Binary logistic regression analysis was used to explore risk factors for CPP, and receiver operating characteristic (ROC) curves were generated to evaluate the diagnostic value of related indexes. Results Sixty patients, including 40 girls with IPT and 20 girls with CPP, were recruited. The prevalence of overweight and obesity in the entire cohort was 25% (15/60) and was significantly higher in IPT than CPP, 32.5% (13/40) vs. 10% (2/20), respectively (P=0.045). There were significant differences in LH, uterine volume, follicle numbers and BA (P<0.05). The impaired PAH of IPT and CPP was 0.01 ± 1.19 SD and 0.62 ± 0.94 SD with significant differences (P=0.047). Logistic regression analysis showed that LH and follicle numbers were independent risk factors for CPP. The ROC curve showed that the area under the curve (AUC) of LH and follicle numbers were 0.823 and 0.697. The sensitivity and specificity of LH with a cut off of 0.285 IU/L were 78.9% and 77.8%. The sensitivity and specificity of follicle numbers with a cut off of 3.5 were 89.5% and 52.8%. Conclusion The prevalence of overweight and obesity in 6- to 8-year-old girls with precocious puberty was high. Auxological data should not be used in the differential diagnosis of IPT and CPP. Basal LH above 0.285 IU/L and follicle numbers greater than 4 were important features suggestive of CPP. PAH was impaired in individuals with CPP, but it was not impaired in individuals with IPT.